Rubber Wood Sawdust Waste Converted to Activated Carbon for Heavy Metal Removal from Wastewater - Kengchuwong, Metta; Ketwong, Chatyapha; Nuasri, Chompoo; Wanich, Suchana; Trisupakitti, Somsuk; Morris, John (Journal of Food Health and Bioenvironmental Science, 2023)
In this study, we characterized activated carbon prepared from rubber wood sawdust waste and determined optimum conditions for removing copper ions from synthetic wastewater. Rubber wood sawdust was calcined at 600°C for 30 min and then activated with commercial vinegar (5%v/v acetic acid) or 5% lime juice for 24 hr. Three characteristics of the activated carbon were evaluated: (i) to study the ability to remove copper ions versus exposure time, pH and the amount of adsorbent, (ii) adsorption isotherms and (iii) adsorption kinetics. A Langmuir isotherm indicated that the activated carbon adsorbed a monolayer of Cu(II) ions, KL = 7.91 mg/L with a capacity to adsorb 0.37 mg Cu(II)/g. The optimum conditions for usage was found at 20 g/L activated carbon in wastewater, pH 5 and 60 min adsorption time. Adsorption kinetics were consistent with a pseudo-second order reaction. The results of the study suggest that converting rubber wood sawdust waste to activated carbon allows it to become useful to remove heavy metal pollutants from wastewater.